Basketball coaches knowledge about hydration - Matkovic, B.; Rupcic, T.; Matkovic, B. R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Water is the nutrient a basketball player needs the most, about 2-3 L/day. As the most largely represented substance in the human body water is a medium where metabolic reactions occur, but it also participates in some. There has been evidence that even dehydration which reduces the body mass by only 2% causes problems during physical activity and a 5% loss of body mass through dehydration decreases the physical working capacity by 30 % (Armstrong and cow; 1985; Saltin & Costill, 1988). Dehydration has proved to have a negative impact on aerobic activities and sprint, to speed up fatigue and, what is particularly significant, affects the ability to play (Burke, Hawley, 1997; Casa and cow; 2000). The aim of this study was to test the basketball coaches` knowledge of hydration. Methods: The sample consisted of 52 Croatian basketball coaches at the age 26 to 53. For this investigation a questionnaire was composed with ten questions regarding the basic principles of hydration. The questionnaire was completed anonymously. The obtained data were analyzed by standard statistical procedures, with statistical software package SPSS 13.0. Results and Discussion: According to the results it is obvious that knowledge about hydration of the coaches is not on adequate level. In general coaches are aware that establishing the balance of body fluids upon activity is a very important part of recovery, and that this is even more important in hot and humid conditions. Fast and full rehydration is extremely important when it comes to tournaments. Rehydration during recovery implies not only the compensation for the lost volume, but also for the lost electrolytes, primarily sodium, that are lost through perspiration during the game. On the other hand most of the coaches have no idea of the amounts or the content of sport drink and they think that thirst is a good parameter of the fluid needs. Very few of the investigated coaches make connection about the rehydration and refilling energy sources. They never heard about the possibility of excessive liquid intake and the possibility of related hyponatremia.